An integrated EK-MFC technology for sludge electro-dewatering & heavy metals removal - Lee, Kah Yong. (2012)
Bioelectricity generation from acetate and anaerobic digestate was examined using dual chambered microbial fuel cell (MFC) containing granular graphite as electrodes and proton exchange membrane (PEM) between the chambers. When acetate was used as the sole substrate, maximum power output of 2 mW was obtained at a current of 5.37 mA, whereas open circuit voltage (OCV) of 622 mV was measured. When acetate was mixed with anaerobic digestate at different ratio, lower power outputs were observed. In general, the higher the percentage of anaerobic digestate in the substrate mixture, the lower the OCV & power output was observed. The maximum power output measured for 100% anaerobic digestate was 0.12 mW, obtained at a current of 0.9 mA. The OCV was measured 208 mV, which was 3 times lower compared to the OCV when 100 % v/v of 1.6g/L acetate was used. Regardless of the substrate composition, COD reduction of more than 50% was achievable for all reactors after 3 days of operation. For all of the reactors, the coulombic efficiency was found to be in the range of 8-15%. Lower coulombic efficiency was observed for reactors with higher percentage of anaerobic digestate in the substrate mixture.